Cash Waqf Literacy in Indonesia: Literature Studies and Perspectives of Islamic Economics Academics - Nurul Jannah; Andri Soemitra (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2022)
Cash waqf in Indonesia has become a topic of discussion in the world of scientific articles, both national and international scientific articles. In addition, cash waqf has also been regulated in law but all of this does not make the literacy of Muslims in Indonesia increase related to cash waqf, this can be seen from the waqf funds collected are not optimal if look at the condition of Muslims in Indonesia. This study uses a qualitative approach to content analysis by using the FGD method as a complement to this research. The results in this study, there is still a lack of public literacy related to cash waqf by looking at several previous studies so that academics provide several strategies and inputs to improve public literacy related to cash waqf, so that people have awareness in cash waqf.